SAT0475 Serum Protein Levels, Fall Occurrence, Bone Fractures and Nutrition in Rheumatic Patients – is There Any Relationship?. (10th June 2014) - Borges, J.; Fernandes, S.; Gonçalves, I.; Cardoso, A.; Simão, R.; Fernandes, R.; Vila, I.; Pires, G.; Barcelos, F.; Cunha-Miranda, L.; Santos, H.; Leitão, R.; et al.
Abstract : Background: Regardless of epidemiologic evidence suggesting a positive impact of protein dietary intake over bone health, the connection between dietary protein and bone metabolism remains controversial. A hyperproteic diet is linked to increased renal calcium excretion but there is no clear evidence of its relevance in the development of osteoporosis (OP). In the elderly, it is often found a low dietary protein intake and association between low serum albumin levels, femoral neck fracture and post-fracture mortality. A correlation between body composition and fall occurrence is under discussion. Objectives: To study the relation between nutritional/biochemical variables and occurrence of falls and fractures. Methods: A questionnaire on dietary protein intake was applied to patients at a Rheumatology clinic during 4 non-consecutive weeks from July to September 2013. Nutritional evaluation included body composition (InBody 720). Clinical data collected included: fall occurrence; history of clinical and/or radiologic vertebral fractures; total serum protein, albumin, inorganic phosphate, calcium, parathyroid hormone, vitamin D and calcium urinary excretion levels and neck/lumbar densitometry. Descriptive statistics, Mann-Whitney, Kruskal-Wallis, Qui-Square and Spearman correlation were applied for a significance of p<0, 05 . Results: 196 subjects were included, 88% female, mean age 58 years. The most prevalent rheumatic diseases were: rheumatoid arthritis (RA), osteoarthritis (OA), Sjögren's syndrome, undifferentiated connective tissue disease, spondyloarthritis, systemic lupus erythematosus (SLE) and fibromyalgia. The average body mass index (BMI) was 27, 5 kg/m 2, higher in patients diagnosed with SLE, OA and RA. 20 subjects (10, 2%) had previous history of fall occurrence, 24 (12, 2%) had history of fractures (7 vertebral, 2 femoral neck, 4 wrist). We found correlation between the occurrence of fractures and female gender (25 vs. 0 patients, p=0, 046); lower T-score at femoral neck (r=-0, 521, p=0, 046) and lower total serum protein levels (6, 39 vs. 6, 69, p=0, 018). These variables were also correlated with the number of fractures . Fall occurrence was higher in older subjects (64, 8 vs. 57, 4 years, p=0, 017), and in those with higher T-score at lumbar spine (r=0, 663, p=0, 014). In subjects over 58 years, we found an association with body percentage and BMI, independent of muscle mass (p<0, 05). There were no differences between the groups with and without fracture concerning nutritional parameters or mean age (62 vs.57, 7 years, p=0, 136). Conclusions: In this population, in a rheumatologic setting, fractures were commoner in women, with lower bone mineral density and lower serum protein levels. Higher BMI and body fat percentage may be risk factors for fall occurrence in the elderly, eventually related to a shift in the centre of gravity. Nutritional advice in OP patients should consider these notions. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4357